E-government. (New York 3G E-LEARNING, 2018)
a. This text provides selected examples of current developments from various countries in terms of technology, applications and services, and various real world m-government examples.
b. Provides an understanding on contemporary experiences on technological, societal and legal setups of e-Government implementation in emerging economies.
c. Covering such issues as e-government adoption and diffusion; social and performance issues of e-government; and information security, privacy, and policy, this book is an essential resource to any library collection.
Chapter 1 Introduction to e-government -- Chapter 2 Information society -- Chapter 3 Strategy of e-government -- Chapter 4 E-government business models -- Chapter 5 E-government services -- Chapter 6 Multichannel e-government strategy -- Chapter 7 E-governance: conceptual framework -- Summary -- References -- Index.
Includes bibliographical references and index
Keywords: Internet in public administration; Electronic government information; Government Web sites